Arctic tourism in times of change: Uncertain futures - from overtourism to re-starting tourism - Jóhannesson, Gunnar Thór; Welling, Johannes; Müller, Dieter K.; Lundmark, Linda; Nilsson, Robert O.; de la Barre, Suzanne; Granås, Brynhild; Kvidal-Røvik, Trine; Rantala, Outi; Tervo-Kankare, Kaarina; Maher, Patrick (Nordic Council of Ministers, 2022)
This report was originally published as: Jóhannesson, G.T., Welling, J., Müller, D.K., Lundmark, L., Nilsson, R.O., de la Barre, S., Granås, B., Kvidal-Røvik, T., Rantala, O., Tervo-Kankare,K., & Maher, P. (2022). Arctic tourism in times of change: Uncertain futures - from overtourism to re-starting tourism. Nordic Council of Ministers. DOI:10.6027/temanord2022-516 This report presents the findings of the third and final workshop and field course hosted by the project Partnership for Sustainability: Arctic Tourism in Times of Change funded by the Nordic Council of Ministers’ Arctic Co-operation Programme 2018–2021. The focus of the workshop was on overtourism and the impact of and response to COVID-19 by companies and stakeholders in Arctic tourism. https://viurrspace.ca/bitstream/handle/10613/25309/delaBarre2022.pdf?sequence=3 This publication was funded by the Nordic Council of Ministers.